2023
DOI: 10.54910/sabrao2023.55.1.12
|View full text |Cite
|
Sign up to set email alerts
|

Biological Significance of Alfalfa in the Development of Organic Farming in South-Eastern Kazakhstan

Abstract: The ecological situation and modern agro-landscape improvement, soil fertility maintenance and uplifting, formation of ecologically safe agro-ecosystems with germplasm diversity in crop rotation, and cultures-soil conditioners are the focus of the study. Nitrogen is a vital element required in larger quantities by plants; however, lack of it has become a problem in organic farming. The presented study suggests ways organic farming can boost up nitrogen in return to address nitrogen deficiency. The research sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…With direct sowing, agronomically valuable aggregates form in optimal quantities; with traditional cultivation technology, the proportion of the pulverized fraction increases, which, in turn, increases the susceptibility of the soil to erode and deflate. In direct sowing, a higher soil water resistance appeared (Volters et al, 2020;Gusev et al, 2022;Bastaubayeva et al, 2023;Kenenbaev et al, 2023). According to Baybekov's (2018) findings, negative consequences occur during dump processing.…”
Section: Structural Condition Of Light Chestnut Soilmentioning
confidence: 99%
See 1 more Smart Citation
“…With direct sowing, agronomically valuable aggregates form in optimal quantities; with traditional cultivation technology, the proportion of the pulverized fraction increases, which, in turn, increases the susceptibility of the soil to erode and deflate. In direct sowing, a higher soil water resistance appeared (Volters et al, 2020;Gusev et al, 2022;Bastaubayeva et al, 2023;Kenenbaev et al, 2023). According to Baybekov's (2018) findings, negative consequences occur during dump processing.…”
Section: Structural Condition Of Light Chestnut Soilmentioning
confidence: 99%
“…In this field, the first successful cultivation of grain crops occurred in Northern Kazakhstan (Karabaev et al, 2005). According to FAO data, in 2009, Kazakhstan entered the top 10 countries with the introduction of zero tillage to 1.5 million ha, and by 2014, the area had increased to two million ha (Karabayev et al, 2015;Gusev et al, 2022;Bastaubayeva et al, 2023;Kenenbaev et al, 2023). However, the introduction of no-till became a preference in non-irrigated lands of Northern Kazakhstan.…”
Section: Introductionmentioning
confidence: 99%
“…Past studies have reported that in addition to provitamin A (carotene), alfalfa contains vitamin В 1 , which prevents diseases of the nervous system and is vital in managing the carbohydrate metabolism in the animal body; vitamin C -antiscorbutic; vitamin Dantirachitic; vitamin K -affecting blood composition (blood clotting); vitamin PPpreventing pellagra in animals, and vitamin Eaffecting the reproductive ability of the animals (Zykov, 1967;Bastaubayeva et al, 2023). The findings of Cui et al (2018) revealed that intercropping can increase plants' biomass and reduce the accumulation of heavy metals in plants.…”
Section: Introductionmentioning
confidence: 99%
“…The abovementioned stress conditions degrade the soil, adversely affecting other microflora organisms, the environment, and human health (Gu et al, 2019;Bastaubayeva et al, 2023). The undesirable properties of fertilizers and pesticides have compelled the search for an option that positively affects soil fertility, allowing for sustainable agriculture that gains positive attention from the farming community -organic fertilizers (Kumar and Madhu, 2016;Gusev et al, 2022;Makenova et al, 2023).…”
Section: Introductionmentioning
confidence: 99%